Requirements for an ubiquitous computing infrastructure - Maffioletti, S. (Культура народов Причерноморья, 2001)
Ubiquitous computing is an emerging paradigm for interactions between people and computers. Its aim is to break away from the desktop computing to provide computational services to a user when and where required. In this paper we present the design criteria for an infrastructure platform for ubiquitous computing applications. The motivation for building such infrastructure is to formalize a common design methodology for developing application based on the notion of Interactive Environment. Вездесущие компьютерные технологии это образец взаимодействия между людьми и компьютерами. Их цель дать возможность пользоваться услугами компьютерных систем там, где этого пожелает пользователь. В статье представлены принципы разработки основы инфраструктуры для применения вездесущих компьютерных технологий. Причиной создания подобной инфраструктуры является формализация общей методологии разработки прикладных программ, основанных на представлении об интерактивной среде. Всюдисущі комп'ютерні технології це зразок взаємодії між людьми і комп'ютерами. Їх мета дати можливість користуватися послугами комп'ютерних систем там, де цього побажає користувач. У статті представлені принципи розробки основи інфраструктури для застосування всюдисущих комп'ютерних технологій. Причиною створення подібної інфраструктури є формалізація загальної методології розробки прикладних програм, заснованих на уявленні про інтерактивну середу.